Structural-Induced Speleogenesis at Karakal-Japyryk Natural Reserve, Kyrgyzstan - Reinhart, Hilary; Haryono, Eko; Barianto, Didit Hadi; Ristiawan, Angga Wahyu; Putra, Rakhmat Dwi; Rabbani, Dimas Irham; Sufi'atun, Dita Marfuah; Saputra, Aan; Lutviah, Hajar; Kulsum, Farah Aida Ilmiatul (Departemen Teknik Geologi, 2019)
Speleogenesis is one of the most essential studies at speleological science. it examines how caves are formed and developed as the fundamental knowledge to comprehend cavity phenomena. These phenomena occasionally occur in karstic landscape where Karakal-Japyryk Natural Reserve, as part of carboniferous limestone in Tien-Shan Mountain is located. Several factors such as climatic, geologic, and biologic factors hold a certain role in speleogenetic process. One of the key roles from geological factor is the presence of geological structures e.g. bedding plane and joint which initiates cavity development.This paper tends to examine the speleogenetic process happens at Karakal-Japyryk Reserve. The speleogenetic process can be described using speleomorphological approach combined with measured stratigraphy and structural study to reconstruct the process happening. Measurement and drawing of cave dimension was also conducted to obtain a visualization of the cave. This study was particularly done at KG-4 and KG-5 cave in Karakal-Japyryk Reserve.From the measurement and analysis, it is known how the geological structures had a strong role in the speleogenetic process. It opened and triggered initial dissolution in limestone which developed into cave. The evidence can be seen through the direction and form of the cave passage which indicates structural influences by its linearity and its correlation with the structure like bedding plane and vertical joints presence at the surface.